Effect of Rayleigh Damping Variation on the Seismic Fragility of Masonry Structures - Upadhyay, Magnus; Kafle, Pradeep; Ban, Sabin; Khakurel, Shreedhar (Journal of Engineering Issues and Solutions, 2026)
Masonry structures in earthquake-prone areas are highly vulnerable because they are often built with weak materials, poor detailing, and limited maintenance, yet their seismic behavior is still not well studied. Damping is one of the parameters that influences seismic performance. It plays a critical role in energy dissipation, but its effect on masonry fragility is not fully understood. This study focuses on the influence of Rayleigh damping variation on the seismic fragility of unreinforced masonry (URM) and reinforced masonry (RM) buildings using a numerical macro- modeling approach. Nonlinear dynamic responses were analyzed under damping ratios ranging from 1% to 6%, and incremental dynamic analyses (IDA) were performed to generate corresponding fragility curves for each damping level. Results show that with an increase in damping ratios there was a reduction in roof displacements and overall seismic response, with URM showing strong sensitivity to Rayleigh damping variation. In contrast to this, RM structures exhibited reduced sensitivity, with damping effects decreasing toward collapse states. Across all damage states, reinforced masonry consistently outperformed unreinforced masonry. These findings showed the need for site- and material-specific damping characterization for URM, whereas standard guideline- based damping ratios are generally sufficient for RM, even at collapse-level fragility. The study highlights the importance of evaluating damping sensitivity in seismic fragility assessments and contributes to improving the reliability of numerical modeling for masonry structures.